A Typology of Source of Information About the Continuing Care Retirement Community and Older Adults' Living Arrangement. Issue 4 (2nd October 2019) - Ayalon, Liat; Gum, Amber
Abstract: A continuing care retirement community (CCRC) represents a residential alternative for older adults. It offers a variety of social and health care services to meet older adults' needs and preferences. Using the theory of innovation as a theoretical basis, the overall goal of the study was to use the source of information about the CCRC as a potential predictor of the decision to move. In total, 76 older adults responded to a question about the source of information on the CCRC. Of these, 40 were CCRC residents and 36 were community dwellers, who expressed an interest in the CCRC but decided to remain in their community. Based on their responses, respondents were classified into one of five clusters (e.g., spouse, friends, children, nonhuman sources, mixed human and nonhuman sources). Those classified into the spouse or adult children as sources of information were more likely to live in a CCRC. Results show that information about the CCRC should be conveyed to additional members in the family, such as adult children, as they often take a major role in the decision to relocated. The findings have implications for administrators as they clearly point to potential sources of greater influence on older adults' decision to relocate.